PENGARUH VIDEO SAMPURAGA UNTUK MENINGKATKAN KEMAMPUAN MEMAHAMI ISI CERITA PADA SISWA KELAS III SDN 113 PEKANBARU - Wulan Pusfian Tika; Laili Rahmi (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This study aims to determine the effect of using the Sampuraga video in improving the ability to understand the story content of third-grade students of SDN 113 Pekanbaru. The background of this study is based on the results of initial observations which show that most students have difficulty in understanding the elements of the story, such as plot, characters, settings, and moral messages. The method used in this study is a pre-experiment with a one-group pretest-posttest design. The sample in this study amounted to 24 students. The instrument used was a multiple-choice test to measure the understanding of the story content. The results showed that the average score of students' pretest was 52.00 and the average score of students' posttest was 80.00. Based on the results of the t-test, a significance value of 0.000 <0.05 was obtained, which means there is a significant difference between the results of the pretest and posttest. The implications of this study indicate that local video-based learning media can be an innovative solution to improve reading literacy and strengthen cultural values in learning Indonesian in elementary schools. Thus, it can be concluded that the use of the Sampuraga video has a positive effect on improving the ability to understand the story content in grade III students of SDN 113 Pekanbaru..